The Relationship between Indonesian Sign Language (BISINDO) and Oral Skills with the Self-Confidence of Deaf Students at SLB B - Priyono; Alexandrin Farah Diba Alexa (Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
Deaf students have low self-confidence due to communication barriers. Hearing impairments make it difficult for them to receive and convey information, especially verbal information. This study aims to analyze the relationships among Indonesian Sign Language (BISINDO), oral skills, and deaf students' self-confidence. This study is a quantitative correlational study with a sample of 34 deaf students at junior high and senior high school levels. Data collection used BISINDO skills tests, oral skills tests, and self-confidence scales. Data analysis techniques used multiple regression analysis. The results showed that BISINDO skills accounted for 51.4% of self-confidence, while oral skills accounted for 25.9%. The effective contribution of BISINDO and oral skills together to self-confidence was 77.3%. It can be concluded that there is a significant positive relationship between BISINDO and oral skills, and between BISINDO and self-confidence, among deaf students at SLB B. These findings highlight the importance of improving BISINDO and oral skills for deaf students' self-confidence. The implications of this research indicate that developing communication skills, both through BISINDO and oral communication, needs to be a primary focus in the education of deaf students. Good mastery of BISINDO can help students express themselves more easily, build social interactions, and increase self-confidence in both school and community settings. Furthermore, oral communication skills are also crucial for supporting broader communication capabilities.